Strengthening Human Rights-Based Legal Protection on Victims of Child Trafficking in Indonesia - et al., Sulistya Eviningrum (International Journal of Advanced Science and Technology, 2019)
This research analyzes the strengthening of human-rights based legal protection on victims of child trafficking. This research is a normative/doctrinal legal research and uses legislative and case study approaches. The law materials used are primary and secondary legal materials. The data of this research were collected by literature reviews. The author uses deductive reasoning by taking into account the concept of law as positive norms in the national legislative system. Based on the results of this research, it can be concluded that: First, there are several factors that make children (especially girls) to be involved in human trafficking. Second, the efforts to strengthen the legal protection and human rights to the victims of child trafficking consists of two ways, namely the strengthening of family resilience as a preventive effort against child trafficking, and the strengthening of legal protection to victims of child trafficking by the principles and arrangements of compensation perspective. The government needs to establish and improve legislation relating to compensation for victims of child trafficking.